2015
DOI: 10.1162/jocn_a_00719
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phase-locking to the Temporal Envelope of Speech in Auditory Perception and Speech Intelligibility

Abstract: The temporal envelope of speech is important for speech intelligibility. Entrainment of cortical oscillations to the speech temporal envelope is a putative mechanism underlying speech intelligibility. Here we used magnetoencephalography (MEG) to test the hypothesis that phase-locking to the speech temporal envelope is enhanced for intelligible compared with unintelligible speech sentences. Perceptual "pop-out" was used to change the percept of physically identical tone-vocoded speech sentences from unintelligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 49 publications
11
87
5
1
Order By: Relevance
“…One seemingly contradictory finding to the present results is reported by Millman et al (2014) who fail to find any effect of intelligibility on the speech-tracking response to tone-vocoded speech. This null effect, which is also in contrast to several previous studies that found effects of intelligibility on sensory processing of speech (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One seemingly contradictory finding to the present results is reported by Millman et al (2014) who fail to find any effect of intelligibility on the speech-tracking response to tone-vocoded speech. This null effect, which is also in contrast to several previous studies that found effects of intelligibility on sensory processing of speech (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study showed that speech-tracking of tone-vocoded speech was not altered even when their intelligibility was increased due to training (Millman et al 2014), suggesting that the mere fact that a stimulus is intelligible does not necessarily enhance its speech-tracking response. Unfortunately, in that study responses to natural speech were not compared to the artificial vocoded stimuli.…”
Section: 2 Effects Of Linguistic Processing On Sensory Responsesmentioning
confidence: 99%
“…Alternatively, our results suggest that during speech listening, low-frequency neural tracking may be weakly modulated by top-down word segmentation processing (Howard and Poeppel 2010;Millman et al 2015;Obleser et al 2012;Peña and Melloni 2012). The small phase differences observed in LFO contrast with the large phase reversals of low-frequency entrainment reported during attentional selection (Besle et al 2011;Gomez-Ramirez et al 2011;Lakatos et al 2008) and cocktail party effects (Zion Golumbic et al 2013).…”
Section: Origins Of the Difference Between Hfa And Lfo Effectsmentioning
confidence: 59%
“…However, and importantly, speech intelligibility was also confounded with changes in the acoustic properties of the speech signal, leaving open the possibility that the observed modulations of LFO were driven by acoustic cues. In fact, in a different series of experiments controlling for acoustic properties, no direct link between speech intelligibility and neural entrainment of LFO was found (Millman et al 2015;Peña and Melloni 2012;Zoefel and VanRullen 2015). All in all, these results suggest that LFO may govern attention and temporal expectation mechanisms that regulate the gain of the acoustic information but may not reflect top-down syllable/word segmentation per se.…”
mentioning
confidence: 73%
“…In the last ten years, studies with M/EEG (magneto/electro-encephalography) have shown the importance of neural oscillations to brain function, providing an alternative and often convergent perspective upon the neural processes involved in speech comprehension. For example, Peelle, Gross, & Davis (2013) showed in MEG that neural oscillations tracking the envelope of speech (between 4 and 7 Hz) were bilateral in response to unintelligible speech, but showed greater phase locking and left lateralization in the case of intelligible signals (though see Millman, Johnson, & Prendergast (2014) for contradictory evidence). Other studies have shown evidence for hierarchical organization of oscillatory activity across frequency bands (Lakatos et al, 2005) and the importance of alpha oscillations (8-13 Hz), localized to temporal as well as parietal and prefrontal cortex, in predicting comprehension ratings of degraded speech (Obleser & Weisz, 2012), strongly paralleling findings from fMRI.…”
Section: Future Directionsmentioning
confidence: 99%